Analysis of Poetic Personality- “Sarojini Naidu” Nightingale of India was a Poet and Politician” - Gulnaz Fatma; Nahla Pirzada; Sameena Begum; Saba Tarique (PT FORMOSA CENDEKIA GLOBAL, 2023)
Sarojini Naidu was a student who excelled academically, a renowned freedom fight activist in India, and a poet who wrote sonnets. She is popularly known as the